Spectral and Magnetic Studies of Cobalt(II), Nickle(II), Copper(II), Zinc(II) and Silver(I) Complexes with 4-(2-Thiazolyl) Thiosemicarbazide - Mishra, Lallan; Singh, V.K.; Agarwala, U.C. (Asian Journal of Chemistry, 2010)
Paramagnetic cobalt(II), nickel(II), copper(II) and diamagnetic zinc(II) and Ag(I) complexes of 4-(2-thiazolyl) thiosemicarbazide (L) of the compositions MLCl2 [M ═ Co(II), Ni(II) and Cu(II)], ZnL2Cl2 and AgLNO3, have been prepared and characterized by spectral (ir, 14N nmr and esr for CuLCl2 only) and magnetic studies as well as by elemental analyses. All of the complexes except Ag(I) have octahedral coordination whereas Ag(I) has tetrahedral arrangement of ligand around it.